Effects of anodal tDCS on electroencephalography correlates of cognitive control in mild-to-moderate traumatic brain injury. - Mertens, Nickolas; Cavanagh, James; Brandt, Emma; Fratzke, Violet; Story-Remer, Jacqueline; Rieger, Rebecca; Wilson, J. Kevin; Gill, Darbi; Campbell, Richard; Quinn, Davin K. (NeuroRehabilitation, 2023)
BACKGROUND: Transcranial direct current stimulation (tDCS) may provide a potential therapy for cognitive deficits caused by traumatic brain injury (TBI), yet its efficacy and mechanisms of action are still uncertain. OBJECTIVE: We hypothesized that anodal tDCS over the left dorsolateral prefrontal cortex (DLPFC) would boost the influence of a cognitive training regimen in a mild-to-moderate TBI (mmTBI) sample. Cognitive enhancement was measured by examining event-related potentials (ERPs) during cognitive control tasks from pre- to post-treatment. METHODS: Thirty-four participants with mmTBI underwent ten sessions of cognitive training with active (n = 17) or sham (n = 17) anodal tDCS to the left DLPFC. ERPs were assessed during performance of an auditory oddball (3AOB), N-back, and dot pattern expectancy (DPX) task before and after treatment. RESULTS: P3b amplitudes significantly decreased from baseline to post-treatment testing, regardless of tDCS condition, in the N-back task. The active tDCS group demonstrated a significantly increased P3a amplitude in the DPX task. No statistically significant stimulation effects were seen during the 3AOB and N-back tasks. CONCLUSION: Active anodal tDCS paired with cognitive training led to increases in P3a amplitudes in the DPX, inferring increased cognitive control. P3b decreased in the N-back task demonstrating the effects of cognitive training. These dissociated P3 findings suggest separate mechanisms invoked by different neuroplasticity-inducing paradigms (stimulation versus training) in brain networks that support executive functioning.